Impact of International Capital Inflows, Institutional Quality, and Macroeconomic Factors on Labour Productivity in Nigeria - Uzoma Mirian Anyachebelu (PT. BATARI EDU CALYA, 2026)
The study is based on the Solow–Swan neoclassical growth model, which explains economic growth through the interaction of output, capital, labour, and technological progress. It examines how international capital inflows influence labour productivity in Nigeria. The model includes variables such as foreign direct investment, foreign portfolio investment, external debt, official development assistance, remittances, gross fixed capital formation, real GDP, and secondary school enrollment. The analysis employs the Autoregressive Distributed Lag (ARDL) approach to capture both short-run and long-run relationships among variables. For robustness, the Fully Modified Ordinary Least Squares (FMOLS) technique is also applied. The study further conducts pre- and post-estimation diagnostic tests to ensure the reliability and stability of the econometric results. The results revealed a mixed order of integration, where four variables were integrated at first difference I(1) and six variables were stationary at level I(0), satisfying the requirement for applying the ARDL bounds test. Short-run ARDL results show that FDI (-0.0023), ODA (-0.0009), external debt (-0.0118), and GFCF (-0.0780) negatively affect labour productivity, while RGDP (1.0221), secondary school enrolment (0.0010), and FPI (0.0000) have positive effects. The error correction term (-0.5823) confirms adjustment toward long-run equilibrium. Diagnostic tests indicate no autocorrelation, no heteroscedasticity, and model stability. The findings suggest that improving institutional quality and macroeconomic stability is essential for ensuring that international capital inflows effectively enhance labour productivity in Nigeria